Psikoedukasi Regulasi Emosi untuk Mengurangi Perilaku Melanggar pada Siswa Melalui Teknik Mindfulness - Fadillah Fira Firmanilah; Diah Ayu Permatasari; Roselina Dwi Hormansyah; Rizkia Hidayati; Kasmayani Karim (Universitas Negeri Makassar, 2026)
Adolescents undergoing a dynamic phase of emotional developmemt often exhibit high levels of impulsivity, which increases their vulnerability to aggressive behavior and rule violations when emotional regulation is inadequate. This study aims to enhance students’ emotion regulation skills in order to reduce rule-breaking behavior through a mindfulness-based psychoeducational program. A psychoeducational intervention was conducted using three stages: preparation, implementation, and evaluation. The participants consisted of 20 students from SMA Kartika XX-1 Makassar with a documented history of disciplinary violations. Data were collected thorugh participants attendance, observation of engagement, and feedback on the program materials. The fingdings indicate that the program was successfully implemented, as evidenced by a 100 % attendance rate, active participation, and predominantly positive responses from participants. Most students reported that the materials were relevant, easy to understand and applicable to their daily lives. Furthermore, participants demonstrated improved emotional awareness, enhanced self-control, and increased motivation to adobt more adaptive behaviors. In conclusion, mindfulness-based psychoeducation is an effective intervention strategy for improving student’s emotion regulation and reducing rule-violating behavior in the school setting. This program also holds strong potential for sustainable implementation as part of broader efforts to support character development and promote students’ mental health.